Reliability of Data Collected by Volunteers: A Nine-Year Citizen Science Study in the Red Sea - Meschini, Marta; Machado Toffolo, Mariana; Marchini, Chiara; Caroselli, Erik; Prada, Fiorella; Mancuso, Arianna; Franzellitti, Silvia; Locci, Laura; Davoli, Marco; Trittoni, Michele; Nanetti, Enrico; Tittarelli, Mara; et al. (Frontiers in Ecology and Evolution, 2021)
The quality of data collected by non-professional volunteers in citizen science programs is crucial to render them valid for implementing environmental resources management and protection plans. This study assessed the reliability of data collected by non-professional volunteers during the citizen science project Scuba Tourism for the Environment (STE), carried out in mass tourism facilities of the Red Sea between 2007-2015. STE involved 16,164 volunteer recreational divers in data collection on marine biodiversity using a recreational citizen science approach. Through a specifically designed questionnaire, volunteers indicated which of the seventy-two marine taxa surveyed were observed during their recreational dive, giving an estimate of their abundance. To evaluate the validity of the collected data, a reference researcher randomly dived with the volunteers and filled in the project questionnaire separately. Correlation analyses between the records collected by the reference researcher and those collected by volunteers were performed based on 513 validation trials, testing 3,138 volunteers. Data reliability was analyzed through 7 parameters. Consistency showed the lowest mean score (51.6%, 95% Confidence Interval CI 44.1-59.2%), indicating that volunteers could direct their attention to different taxa depending on personal interests; Percent Identified showed the highest mean score (66.7%, 95% CI 55.5–78.0), indicating that volunteers can correctly identify most surveyed taxa. Overall, results confirmed that the recreational citizen science approach can effectively support reliable data for biodiversity monitoring when carefully tailored for the volunteer skills required by the specific project. The use of a recreational approach enhances massive volunteer participation in citizen science projects, thus increasing the amount of sufficiently reliable data collected in a reduced time.